Primary Colonic Diffuse Large B-Cell Lymphoma in Bloom Syndrome. Issue 2 (1st February 2022) - Benanzer, Tessa M.; Kamboj, Amrit K.; Sweetser, Seth
ABSTRACT: Bloom syndrome is an inherited disorder involving a characteristic phenotype of short stature, photosensitive rash, immunodeficiency, and an early predisposition to various cancers, including lymphoma and colorectal neoplasms. We present a patient with Bloom syndrome found to have a colonic mass secondary to diffuse large B-cell lymphoma highlighting the importance of cancer screening and surveillance in these patients.